TINJAUAN SISTEM CAISSON PADA PENYAMBUNGAN BLOK LAMBUNG KAPAL - Bambang Sudjasta (Bina Teknika, 2016)
To spur the development of the shipbuilding industry efficient and effective, then one will have to do is select the appropriate application of technology to existing conditions. Selection of the technology is closely related to the technical aspects in the field. National shipyards often get the order the construction of new ships with a capacity that exceeds the shipyard conditions. Based on limited means, but the implementation of the construction of ships should still be able to walk then attempted to carry out the connection of the hull below the water. With theadoption of block module, where assembly of the hull is divided into two parts, the module block bow and stern module block. Block modules separate hull is launched / lowered into the water, and then later made the connection in the water. As tools for splicing in the water system been caisson. Serves as a tool in connecting module block in the water then the caisson system must meet requirements such as: 1. The shape of the surface to be attached to the hull should have the same shape as the shape of the ship body. 2. Structure of the caisson to be strong enough. 3. The caissons must have stability and buoyancy are pretty good. In planning is the preparation before the second block of the module is launched into the waters, such as: 1. Determination of the number and dimensions of the hinge. 2. Determination of welding procedures. The process of implementing these connections include: 1. Control of the position of the module block such that the connections between the two. 2. Installation of the amplifier while. 2. Installation of the caisson continued process of welding the hull. 3. Examination of the results of the weld joint.